Questionnaire pour enquete aupres des jeunes descolarises et non scolarises a lage de 19 a 22 ans (Making a Living: Learning Trajectories Towards the Ability to earn a Livelihood, 2019)
tables and graphs in color
Keywords: Youth; Learning